Determining the need for a breast cancer awareness educational intervention for women with mild/moderate levels of intellectual disability: A qualitative descriptive study. (7th April 2022) - Walsh, Susan; Hegarty, Josephine; Lehane, Elaine; Farrell, Dawn; Taggart, Laurence; Kelly, Louise; Sahm, Laura; Corrigan, Maria; Caples, Maria; Martin, Anne Marie; Tabirca, Sabin; Corrigan, Mark A.; et al.
Abstract: Objective: Following a review of the existing body of literature, this study aimed to explore the need for a breast cancer awareness intervention specifically targeted at women with mild/moderate levels of intellectual disability (ID) and provide perspectives on the preferred processes and content underpinning an intervention. Methods: A qualitative, descriptive design using semi‐structured, individual ( n  = 5) and focus group ( n  = 5) interviews were used to engage with a non‐probability, purposive sample of key stakeholders ( n  = 25) including women with mild/moderate levels of ID, caregivers and healthcare professionals. Data were analysed using qualitative content analysis. Results: Findings highlighted that an educational intervention should focus on breast awareness as opposed to breast cancer awareness. Additionally, findings identified that a combined breast awareness and healthy living intervention could be effective. However, the intervention needs to have a multimodal, hands‐on, person‐centred approach to learning which is underpinned by theory. Furthermore, integrating the caregivers and healthcare professionals into the intervention is recommended. Conclusion: Findings from this study provide a foundation for developing and implementing a theoretically underpinned, multimodal, breast awareness and healthy living educational intervention for women with mild/moderate levels of ID.